A124: Hepcidin as a Predictor of Evolution of Anemia of Chronic Disease to a Macrophage Activation Syndrome in Children With Juvenile Idiopathic Arthritis. Issue Volume 66:Issue(2014)supplement 3 (March 2014) - Egorov, Andrey; Fedorova, Elena; Chasnyk, Vyacheslav; Kostik, Mikhail; Snegireva, Ludmila; Kalashnikova, Olga; Dubko, Margarita; Masalova, Vera; Likhacheva, Tatyana
Abstract : Background/Purpose: Anemia of chronic disease (ACD), also referred to as anemia of inflammatory response, is an anemia seen in chronic illnesses, particularly—in JIA. Now it is suggested to be mostly the result of the hyperproduction ofhepcidin which in turn is a result of influence of proinflammatory cytokines, primarily—IL‐6 considered to be the primary cause of anemia in patients with JIA (Tanaka, Kishimoto, 2012). However, IL‐6 blockers itself may provoke the onset of Macrophage Activation Syndrome (MAS) (Kobayashi et al., 2011), manifesting, particularly, also with anemia. In view of the fact that macrophages involved in MAS express CD163—a scavenger receptor that binds hemoglobin‐haptoglobin complexes—and trigger the pathways which are important for adaptation to oxidative stress induced by free iron (Grom, Mellins, 2010) we can consider hepcidin as a welcome challenge to predict the development of MAS early in the course of the disease. Objective of this study was to assess the possibility to use the serum hepcidin level for predict development of MAS in children with JIA. Methods: 25 children with polyarticular and systemic onset JIA and ACD were studied. Laboratory tests (complete blood count, erythrocyte sedimentation rate, C‐reactive protein, total serum iron, serum ferritin, and total iron binding capacity, soluble transferrin receptor and serum hepcidin) and standard clinical parameters were monitored at the beginning of treatment, and during its course. To evaluate the prognostic value of serum hepcidin level factorial regression was used with hemoglobin concentration and red blood cells count in blood as dependent variables and 26 sets of clinical and laboratory signs including serum hepcidin level as independent variables. Results: Combination of concentrations of hepcidin, ferritin and soluble transferrin receptor had the most prognostic value. The response surface analysis revealed a non‐linear pattern with a ridge making possible to predict evolution of anemia to MAS under a combination: hepcidin <140 ng/mL and ferritin >160 μg/L. The following combinations were associated with high probability of evolution of ACD to a severe form, but not to MAS: 1. hepcidin >200 ng/mL and ferritin <140 μg/L; 2. hepcidin >140 ng/mL and soluble transferrin receptor <1.6 mg/L; 3. hepcidin >140 ng/mL and total iron binding capacity >46 mcmol/L. Mean corpuscular hemoglobin was a more sensitive predictor than the level of hemoglobin Conclusion: Identified risk zones for evolution of anemia to MAS or to a severe form of ACD have rather good explanations in terms of known theoretical concepts of iron metabolism. Attention should be paid to anemia associated with low levels of hepcidin in combination with high levels of ferritin, which can be regarded as a predictor of evolution to MAS in patients with JIA. The resulting numerical characteristics may be considered as indicative, and require verification on a larger sample. Better definition of MAS and more numerous study groups will help to calculate sensitivity and specificity of the prognostic accuracy.